Cutting through barriers: the impact of chinese paper cutting on student engagement in Mandarin language learning / Chong Geeng Ling, Teoh Joo Tong and Fatin Aliyah Hassan - Chong, Geeng Ling (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Globalisation has created a substantial demand for multilingual individuals who can bridge cultural and linguistic divides. As businesses and communities become more interconnected, proficiency in multiple languages, particularly those of global significance like Mandarin, has become essential. In response to these global needs, the Malaysia Education Development Plan 2015-2025 has highlighted the importance of learning additional languages, including Mandarin, to better equip students for the challenges of a globalised world. Learning a new language goes beyond mastering the grammatical structures and vocabulary; it also involves understanding the cultural context in which the language is used. Thus, it is crucial to integrate cultural elements into the Introductory Mandarin curriculum to facilitate a more comprehensive approach to Mandarin language learning.